PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE 5E UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII5 SMPN 25 PEKANBARU - Rahmia Mulya Fitri; Sehatta Saragih; Syofni Syofni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research is a class action research that aims to improve the learning process and to increase the outcomes of mathematics learning of the students by applying learning cycle 5E. The subjects of this research are the students of class  SMPN 25 Pekanbaru at the second semester of academic years 2017/2018 which total number of participants are 35 students, consists of 20 male students and 15 female students with heterogeneous academic achievements. This research has two cycles. Each of them has four stages: planning, implementation, observation, and reflection. The data collecting instruments consist observation sheet (learning process) and the students' worksheet. Learning device used in this research consists of Syllabus, Lesson plan, and Student work sheet. The data were analized by narrative descriptive and statistical descriptive analysis. The data were obtained from the observation sheets of teacher and students activities that showed the learning process has improved after the model being implemented. From the data of the student’s evaluation test, it showed that the number of students who reach with Minimal Score of Criteria is 75, increased from the basic score to the Quiz I, from Quiz I to Quiz II. In addition, the percentage of students who achieved KKM from basic score to quiz I increased by 14,29% and from quiz I to quiz II increased by 25,71%. In conclusion, the implementation of discovery learning model can improve the learning process and increase the outcomes of mathematics learning of the students of grade  SMPN 25 Pekanbaru at the second semester of academic years 2017/2018  on rectangular and triangular materials.  Key Words : The outcomes of mathematics learning, Learning Cycle 5E, class action research